Impact on aquatic environmental assets: aftermath of december 2014 east coast states of malaysia flood. a study on impact on coral reef ecosystems and intertidal benthos population ecosustainability the management time' - Farid, Che Ghazali (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2017)
The impact on coastline and aquatic ecosystem from the worst ever North East monsoonal flooding event in Malaysia history in years, December 2014 to January 2015 'Tsunami mud-like' flood, in east coast Malaysia can range from unnoticeable to devastating. Floods can accelerate fluxes; destroy drainage and reverine systems causing raw sewage, nutrients and sediments to spill out into bodies of water that may have detrimental influence to east coast Malaysia coral reef structure and dynamics, especially of its benthic populations and marine ecosystems. The plumes effect coral reefs by burying decreasing light levels of depleting oxygen supplies by introduction of large amounts of organics settlements. In pertinent to this the link between water quality parameters and its plankton species composition and prevalence into the system is also unknown. Globally, floods destroy drainage and reverine systems causing raw sewage to spill out into bodies of water. As such nutrients and sediments from east coast coastal rivers may have detrimental influence and be harmful to the majestic east coast Malaysia marine park coral reef especially on the structure and dynamics of benthic populations and marine ecosystems. In Pertinent to Kelantan, its Kelantan river system flows northward thus passing through such major towns as Kuala Krai, Tanah Merah, Pasir Mas and Kola Bharu, before finally discharging into the South China Sea. The 2014 flood was purported as the most significant natural disaster in Malaysia in terms of frequency, area extent, population affected bad damage. Coral reefs are often referred to as the 'rainforests of the sea', although, although one could points out equally well and call rainforests the coral reefs of the land (Davidson, 1998). Regardless, these two ecosystems do indeed share several important attributes, most notably high diversity and severe declines worldwide over the last several decades. Over the past 30 years coral bleaching has become a widespread phenomenon and is now seen by many as one of the most distinct manifestations of climate change impacts on natural ecosystems. Coral bleaching can be a short-lived phenomenon; and its spatial appearance can vary considerably. Some bleaching events are comprehensive and tightly synchronised (i.e., most species fully bleached at the same time) and these are likely to be easier to detect, particularly in areas of high coral cover. Where only some colonies are bleached, or where the loss of colour in bleached colonies is only partial, detection becomes increasingly challenging.